PAIKEM-Based Positive Reinforcement Shaping Technique Against Separation Anxiety in Early Childhood - Kadek Mahadevi; Didith Pramunditya Ambara (Universitas Pendidikan Ganesha, 2023)
Education in Indonesia still has problems that occur, especially the behavior of separation anxiety from attachment figures, this was found from observations by researchers, which are influenced by self and environmental factors. This study aims to analyze the effect of the PAIKEM-based Shaping technique with Positive Reinforcement on separation anxiety in early childhood. This type of research was a single case experimental design which was carried out in three phases, namely the baseline phase (A1), the intervention phase (B) and the baseline phase (A2). The subject in this study was one child in group A. Collecting research data on children's separation anxiety behavior used observation and interview methods with an observation checklist sheet instrument. The research data were analyzed using descriptive statistical analysis methods and the data presented visually (visual inspection) in graphical form. The results of data analysis showed that there was a decrease in the frequency of separation anxiety and an increase in the frequency of children's anxiety from the baseline phase (A1) with an average of 6 to 14.18 in the intervention phase (B) and an increase in the frequency of children's independence during the PAIKEM-based positive reinforcement technique intervention. prohibited (A2) with an average of 18.7. Based on the results of this study it can be interpreted that the PAIKEM-based positive reinforcement technique has had an effect on reducing children's separation anxiety.